Perovskite thin film prepared by a thiazole derivative additive, and a trans-perovskite solar cell and a preparation method thereof

CN122995507APending Publication Date: 2026-10-27JIANGXI SCI & TECH NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610908287.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

(1)晶面取向调控能力有限:多数添加剂对晶面取向的选择性较弱,难以同时实现(100)/(200)晶面的显著增强,导致薄膜仍存在较多不利晶界

Benefits of technology

1、本发明在钙钛矿前驱体溶液中引入的添加剂分子为(Z)-2-(2-氨基-4-噻唑基)-2-(甲氧基亚氨基)乙酸乙酯(ATTBA),其结构中含有噻唑环(含硫、氮原子)、氨基、甲氧亚氨基和酯基,通过多官能团的协同作用,实现了对反式钙钛矿太阳能电池中钙钛矿吸收层结晶过程的有效调控与缺陷钝化,显著提升了薄膜质量与器件性能。具体而言,该分子中噻唑环的硫原子和氮原子具有丰富的孤对电子,能够与钙钛矿(100)晶面形成最强的选择性结合,优先降低(100)晶面的表面能,从而在结晶过程中通过“最低能量原则”选择性诱导钙钛矿晶核沿(100)晶面取向生长,促进(100)/(200)晶面择优取向;其次,该添加剂能够与钙钛矿前驱体(如FAI、PbI2)发生加合反应和氢键作用,在钙钛矿结晶过程中升高反应能垒、延缓结晶速率,延长晶体生长窗口,获得晶粒尺寸更大、晶界密度更低的致密薄膜;此外,ATTBA分子中的氨基可与甲脒阳离子形成氢键,抑制FAI在高温退火过程中的分解;噻唑环中的硫、氮原子以及甲氧亚氨基、酯基中的氧原子可与未配位的铅离子(Pb2+)形成多齿配位键,氨基可与有机阳离子空位形成氢键,从而实现晶界和体相缺陷的多靶点协同钝化,显著降低非辐射复合损失,提升器件开路电压与填充因子;同时,ATTBA分子中含有的噻唑环等结构赋予其一定的疏水性,有助于增强钙钛矿层在高湿度环境下的稳定性。最终,借助其多官能团的协同作用,ATTBA有效延缓并调控了钙钛矿的结晶动力学过程,促进(100)/(200)晶面择优取向生长,获得了晶粒尺寸更大、缺陷密度更低、疏水性更强的高质量钙钛矿薄膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995507A_ABST
    Figure CN122995507A_ABST
Patent Text Reader

Abstract

The application discloses a perovskite thin film prepared by a thiazole derivative additive, a trans perovskite solar cell and a preparation method, and relates to the technical field of photoelectric materials and devices. The application provides application of a thiazole derivative additive in preparation of a perovskite thin film, wherein the thiazole derivative additive is (Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino) ethyl acetate (ATTBA); the application also provides a perovskite thin film and a trans perovskite solar cell containing the additive. The application introduces ATTBA into a perovskite precursor solution, the structure of the ATTBA contains a thiazole ring (containing sulfur and nitrogen atoms), an amino group, a methoxy imino group and an ester group, and through synergistic effect of the multiple functional groups, effective regulation and defect passivation of a crystallization process of a perovskite absorption layer in the trans perovskite solar cell are realized, the thin film quality and the device performance are significantly improved, and the battery has excellent photoelectric conversion efficiency and long-term stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optoelectronic materials and devices, specifically to a perovskite thin film prepared with a thiazole derivative additive and an inverted perovskite solar cell, as well as a preparation method thereof. Background Technology

[0002] Organic-inorganic halide perovskite solar cells have developed rapidly in recent years, with certified photoelectric conversion efficiency increasing rapidly from 3.8% in 2009 to over 27%, demonstrating their enormous potential as the next generation of photovoltaic technology. Among them, the inverted (pin) structure has become a hot topic in industrialization research due to its advantages such as low-temperature fabrication, low hysteresis, and compatibility with tandem cells.

[0003] Perovskite light-absorbing layers are typically prepared using solution methods, and their crystallization process and film quality directly determine device performance. However, the polycrystalline nature of perovskite films results in numerous defects at grain boundaries and surfaces, including uncoordinated lead ions, organic cation vacancies, and halide ion vacancies. These defects readily act as non-radiative recombination centers, leading to carrier recombination losses and accelerating the degradation of perovskite materials under environmental stresses such as heat, light, and humidity, thus limiting further improvements in device efficiency and stability.

[0004] To overcome the aforementioned technical bottlenecks, researchers generally employ additive engineering strategies, introducing functional additives into perovskite precursor solutions to regulate the crystallization process, passivate defects, and optimize film quality. Among these, small organic molecule additives containing Lewis base groups (such as carbonyl, sulfonyl, and amino groups) have attracted widespread attention due to their ability to coordinate with lead ions. For example, studies have shown that introducing ethyl 2-(2-aminothiazol-4-yl)-2-hydroxyiminoethyl (EHA) into PbI2 precursor solutions utilizes its multidentate coordination effect to connect and integrate PbI2 colloidal clusters, achieving pre-aggregation in the PbI2 precursor solution and promoting subsequent crystal growth of perovskite films. Furthermore, heterocyclic compounds such as thiazoles and pyridines have also been proven to effectively regulate the crystal growth of perovskite films, passivate crystal defects, and improve film quality. In terms of crystal orientation control, research at Northwestern Polytechnical University used environmentally friendly 2-pentanol as a solvent and introduced the functional molecule thiazole derivative 2-(dimethylaminomethyl)-4-(2-aminoethylthiomethyl)thiazole (DAT) to achieve precise control of perovskite crystal nucleation kinetics, resulting in a film with a preferred (100) crystal orientation. Research at Wuhan University of Technology introduced 5-aminothiazole hydrochloride (5ATCl) and utilized its electron acceptor (NH3) + The quality of perovskite thin films is improved by using electron donor (C=N) functional groups.

[0005] Despite the progress made in the above research, existing thiazole additives still have the following shortcomings: (1) Limited ability to control crystal orientation: Most additives have weak selectivity for crystal orientation, making it difficult to achieve significant enhancement of (100) / (200) crystal planes at the same time, resulting in the presence of many unfavorable grain boundaries in the film.

[0006] (2) The effects of crystallization delay and grain size increase are not synergistic: Some additives can delay crystallization, but the increase in grain size is not obvious; or the grain size increases but the crystallization rate is too fast, resulting in poor film uniformity.

[0007] (3) Single functional group for defect passivation: Most additives contain only 1 to 2 active functional groups (such as only amino or only carboxyl groups), which cannot achieve multi-target synergistic passivation and are ineffective against Pb. 2+ FA + I - It lacks comprehensive coverage of various defects.

[0008] (4) Limited improvement in stability: Existing additives mainly focus on initial efficiency, and their effect on improving long-term thermal and wet stability is insufficient, making it difficult to meet commercialization requirements.

[0009] Therefore, it is necessary to further optimize the molecular structure of thiazole additives. How to achieve the triple functions of precise control of crystal orientation, optimization of crystallization process kinetics, and multiple passivation of defects in a single additive molecule through reasonable molecular design, thereby comprehensively improving the efficiency and stability of perovskite solar cells, remains a key technical problem that urgently needs to be solved in the field of perovskite photovoltaics. Summary of the Invention

[0010] The purpose of this invention is to at least solve one of the technical problems existing in the prior art, and to develop a multifunctional additive that can simultaneously achieve preferred crystal orientation control, crystallization process optimization, multi-target defect passivation, and stability improvement. This invention provides a novel thiazole derivative additive and provides perovskite thin films and inverted perovskite solar cells prepared with this thiazole derivative additive. It can achieve multi-target control and defect passivation of the crystallization process of perovskite thin films, thereby obtaining high-quality perovskite thin films and ultimately improving the photoelectric conversion efficiency and long-term stability of inverted perovskite solar cells.

[0011] This invention provides a thiazole derivative additive as a perovskite precursor additive, specifically (Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino)ethyl acetate (ATTBA), whose structure contains a thiazole ring, an amino group, a methoxyimino group, and an ester group. The thiazole derivative additive of this invention can selectively promote the orientation of the (100) / (200) crystal plane of perovskite, while simultaneously slowing down the crystallization rate and increasing the grain size. Furthermore, it passivates grain boundaries and surface defects through the synergistic effect of multiple functional groups. When applied to inverted perovskite solar cells, it can significantly improve photoelectric conversion efficiency and long-term stability.

[0012] The technical solution of the present invention is as follows: In a first aspect, the present invention provides the application of a thiazole derivative additive in the preparation of perovskite thin films, wherein the thiazole derivative additive is (Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino)ethyl acetate.

[0013] This invention introduces ATTBA additive into the perovskite precursor, utilizing the synergistic effect of its multifunctional groups to achieve several effects significantly superior to existing technologies. First, the thiazole ring (sulfur and nitrogen atoms) in the ATTBA molecule can selectively bind to the (100) crystal plane of perovskite, preferentially reducing the surface energy of this plane. This induces the crystal nuclei to grow along the (100) crystal plane during crystallization, promoting the preferred orientation of the (100) / (200) crystal plane, as clearly confirmed by XRD patterns. Second, ATTBA can coordinate and hydrogen bond with precursor components (such as FAI and PbI2), increasing the crystallization reaction energy barrier and slowing the crystallization rate, thereby extending the crystal growth window and significantly increasing the grain size, resulting in a denser film with fewer grain boundaries. Furthermore, multiple functional groups in the ATTBA molecule can synergistically passivate different defects: the sulfur / nitrogen atoms of the thiazole ring and the oxygen atoms of the ester group can form polydentate coordination bonds with uncoordinated lead ions, and the amino group can form hydrogen bonds with organic cation vacancies, thereby significantly reducing the defect state density, suppressing nonradiative recombination, and improving the open-circuit voltage and fill factor of the device. Finally, due to the reduction of defects and the hydrophobicity of the ATTBA molecule itself, the long-term stability of the device is greatly improved. In summary, the inverted perovskite solar cell prepared in this invention exhibits excellent photoelectric conversion efficiency and long-term stability.

[0014] In a preferred embodiment of the present invention, the method of application includes: adding the thiazole derivative additive to a perovskite precursor solution to prepare a perovskite thin film; In the perovskite precursor solution, the concentration of the thiazole derivative additive is 3.0–5.0 mg / mL.

[0015] In a second aspect, the present invention provides a perovskite thin film containing a thiazole derivative additive, characterized in that, The thiazole derivative additive is (Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino)ethyl acetate; The perovskite thin film has the structural formula ABX3, where A is an organic cation or metal ion selected from CH(NH2)2. + CH(NH2)2 + and Cs + One or more of them, B is selected from Pb 2+ Sn 2+ One or more of them, where X is I - ,Br - and Cl - One or more of them.

[0016] In a preferred embodiment of the present invention, the preparation method includes the following steps: Preparation of perovskite precursor solution; The thiazole derivative additive was added to the perovskite precursor solution to obtain a mixture; The mixture is coated onto a substrate, an antisolvent is added dropwise, and the mixture is annealed to obtain the perovskite film.

[0017] In a preferred embodiment of the present invention, the preparation method includes the following specific steps: Formamidin hydroiodide and lead iodide were dissolved in DMF / DMSO solvent to obtain a perovskite precursor solution; The thiazole derivative additive was dissolved in DMSO to obtain an additive solution; The additive solution is dissolved in the perovskite precursor solution to obtain a mixture; The mixture is coated onto a substrate with an interface modification layer. The mixture is then spin-coated at 4000-5000 rpm for 30-50 seconds. An antisolvent is added dropwise in the last 10-15 seconds, followed by annealing to obtain the perovskite film. The antisolvent includes at least one of anisole, chlorobenzene, and diethyl ether; In a preferred embodiment of the present invention, the annealing method includes heating at 100°C to 150°C for 30 to 60 minutes.

[0018] Thirdly, the present invention provides an inverted perovskite solar cell, comprising the aforementioned perovskite thin film.

[0019] In a preferred embodiment of the present invention, the inverted perovskite solar cell comprises, from bottom to top, a transparent conductive substrate layer (such as ITO, FTO or AZO), a hole transport layer (such as NiOx, MEO-4PACz, etc.), an interface modification layer (optional), the aforementioned perovskite absorber layer containing ATTBA, a passivation layer (such as PEAI, etc.), an electron transport layer (such as PCBM), a buffer layer (such as BCP), and a metal back electrode layer (such as Ag, Au, etc.).

[0020] In a preferred embodiment of the present invention, the inverted perovskite solar cell further includes a transparent conductive substrate layer, a composite hole transport layer, a passivation layer, an electron transport layer, and a metal back electrode layer. The material of the transparent conductive substrate layer is selected from any one or more of indium tin oxide, fluorine-doped tin oxide, and aluminum-doped zinc oxide. The composite hole transport layer comprises a hole transport layer, an interface modification layer, and an insulating modification layer arranged sequentially. The hole transport layer is made of nano-nickel oxide, the interface modification layer is made of one or more of MEO-4PACz, MEO-2PACz, and 4PADCB, and the insulating modification layer is made of Al2O3. The material of the passivation layer is selected from any one or more of phenethyl ammonium iodide, 1,3-diaminopropane dihydroiodate, piperazine dihydroiodate, and piperazine hydroiodate. The material of the electron transport layer is selected from any one or more of PCBM, C60, BCP, and SnO2; The material of the metal back electrode layer is selected from one or more of Ag, Au, and Cu.

[0021] In a preferred embodiment of the present invention, the band gap of the inverted perovskite solar cell is 1.56 eV.

[0022] Fourthly, the present invention provides a method for preparing the aforementioned inverted perovskite solar cell, the method comprising: S1. Clean the transparent conductive substrate layer; S2. Preparation of the composite hole transport layer: Prepare an aqueous solution of 18-22 mg / mL nickel nanoparticles, spin-coat it onto a transparent conductive substrate at 2500-3500 rpm for 25-35 s, and then anneal it at 145-155℃ for 25-35 min; Prepare an ethanol solution of 0.4-0.6 mg / mL MEO-2PACz, spin-coat it onto a transparent conductive substrate coated with nickel nanoparticles at 2500-3500 rpm for 25-35 s, and anneal it at 95-105℃ for 5-15 min to form an interface modification layer; Prepare an Al2O3 dispersion, spin-coat it onto a transparent conductive substrate coated with MEO-2PACz at 3500-4500 rpm for 25-35 s, and anneal it at 95-105℃ for 10-20 min; S3. Preparation of perovskite thin film: Formamidinium hydroiodate, lead iodide, methylamine hydrochloride, cesium iodide, and methylamine iodide are dissolved in DMF / DMSO solvent to obtain a perovskite precursor solution; the thiazole derivative additive is dissolved in DMSO to obtain an additive solution; the additive solution is dissolved in the perovskite precursor solution to obtain a mixture; the mixture is coated on a substrate with an interface modification layer; the interface modification layer is first spin-coated at 4000~5000 rpm for 40~50s; the antisolvent is added dropwise in the last 10~15s; and the mixture is heated at 100℃~150℃ for 30min~60min to obtain the perovskite thin film. S4. Preparation of passivation layer: Dissolve phenylethyl ammonium iodide in isopropanol, spin coat it on the perovskite film at a speed of 2500~3500 rpm for 25~35 s, and then anneal it at 65~75℃ for 4~6 min to obtain the passivation layer. S5. Preparation of electron transport layer and buffer layer: Dissolve PCBM in chlorobenzene, spin coat it on the passivation layer at a speed of 1500~2500 rpm for 25~35 s, and then anneal it at 85~95℃ for 25~35 min to obtain electron transport layer. Dissolve BCP in ethanol and spin coat it onto the electron transport layer at a speed of 4500~5500 rpm for 25~35 s to obtain a buffer layer; S6. Preparation of metal electrodes: Cathode silver is deposited on the buffer layer, with a total silver film thickness of 80~120 nm, to obtain an inverted perovskite solar cell.

[0023] In a preferred embodiment of the present invention, S3, preparation of a perovskite thin film: 1.6 mol of lead iodide, 1.6 mol of formamidinium hydroiodate, 0.075 mol of cesium iodide, 0.15 mol of methylamine iodide, and 0.1875 mol of methylamine hydrochloride are dissolved in 1 mL of a solvent containing N,N-dimethylformamide and dimethyl sulfoxide, wherein the volume ratio of DMF to DMSO is 4:1. The mixture is stirred at room temperature for about 20 h to obtain a perovskite precursor solution; the thiazole derivative additive is dissolved in DMSO to obtain an additive solution; the additive solution is dissolved in the perovskite precursor solution to obtain a mixture; the mixture is coated onto a substrate with an interface modification layer, and the interface modification layer is first spin-coated at a speed of 4000~5000 rpm for 40~50 s, and an antisolvent is added dropwise in the last 10~15 s. After spin-coating, the conductive substrate is placed on a hot plate at 100°C. Heating at 150℃ for 30 to 60 minutes and then cooling to form a perovskite film, thus obtaining the perovskite film.

[0024] This invention has at least one of the following beneficial effects: 1. The additive molecule introduced into the perovskite precursor solution in this invention is (Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino)ethyl acetate (ATTBA), which contains a thiazolyl ring (containing sulfur and nitrogen atoms), an amino group, a methoxyimino group, and an ester group. Through the synergistic effect of multiple functional groups, the crystallization process of the perovskite absorber layer in inverted perovskite solar cells and defect passivation are effectively controlled, significantly improving the thin film quality and device performance. Specifically, the sulfur and nitrogen atoms in the thiazole ring of this molecule have abundant lone pairs of electrons, which can form the strongest selective bond with the (100) crystal plane of perovskite, preferentially reducing the surface energy of the (100) crystal plane. Thus, during the crystallization process, the perovskite nuclei are selectively induced to grow along the (100) crystal plane orientation through the "lowest energy principle," promoting the preferred orientation of the (100) / (200) crystal plane. Secondly, this additive can undergo addition reactions and hydrogen bonding with perovskite precursors (such as FAI and PbI2), raising the reaction energy barrier, slowing down the crystallization rate, and extending the crystal growth window during the perovskite crystallization process, resulting in a dense film with larger grain size and lower grain boundary density. In addition, the amino group in the ATTBA molecule can form hydrogen bonds with the formamidinium cation, inhibiting the decomposition of FAI during high-temperature annealing. The sulfur and nitrogen atoms in the thiazole ring, as well as the oxygen atoms in the methoxyimino and ester groups, can react with uncoordinated lead ions (PbI2). 2+ATTBA forms multidentate coordination bonds, and the amino group can form hydrogen bonds with the organic cation vacancies, thereby achieving multi-target synergistic passivation of grain boundaries and bulk defects, significantly reducing non-radiative recombination losses, and improving the open-circuit voltage and fill factor of the device. At the same time, the thiazole ring and other structures contained in the ATTBA molecule endow it with certain hydrophobicity, which helps to enhance the stability of the perovskite layer in a high humidity environment. Finally, with the synergistic effect of its multifunctional groups, ATTBA effectively delays and regulates the crystallization kinetics of perovskite, promotes the preferred orientation growth of the (100) / (200) crystal plane, and obtains high-quality perovskite films with larger grain size, lower defect density, and stronger hydrophobicity.

[0025] 2. The inverted perovskite solar cell prepared by this invention has excellent photoelectric conversion efficiency and long-term stability. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the structure of the inverted perovskite solar cell in Example 1.

[0027] Figure 2 The graph shows the average efficiency of the perovskite solar cells prepared in Comparative Example 1, Example 1, and Comparative Example 4.

[0028] Figure 3 The average efficiency graphs are for the perovskite solar cells prepared in Comparative Examples 1, 2, 3, and 1.

[0029] Figure 4 The Fourier transform infrared spectrum is the result of the interaction between the ATTBA additive in Example 1 and the FAI in the perovskite precursor solution.

[0030] Figure 5 The Fourier transform infrared spectrum shows the interaction between the ATTBA additive in Example 1 and PbI2 in the perovskite precursor solution.

[0031] Figure 6 The image shows a SEM image of the perovskite absorber layer prepared in Comparative Example 1.

[0032] Figure 7 This is a SEM image of the perovskite absorber layer prepared in Example 1.

[0033] Figure 8 The PL spectra of the perovskite absorber layers prepared in Example 1 and Comparative Example 1 are shown.

[0034] Figure 9 The JV curves are for the perovskite solar cells prepared in Example 1 and Comparative Example 1.

[0035] Figure 10 The figure shows the stability test results of the inverted perovskite solar cells prepared in Example 1 and Comparative Example 1. Detailed Implementation

[0036] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0037] The ethyl (Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino)acetate (ATTBA) and ethyl (2-(2-amino-4-thiazolyl)-2-oxoacetate (EAOA) used in the following examples were purchased from Aladdin Reagents.

[0038] Example 1 This embodiment provides an inverted perovskite solar cell with an ITO / NiO structure. x / MEO-2PACz / Al2O3 / Perovskite absorber layer (containing ATTBA) / PEAI / PCBM / BCP / Ag, such as Figure 1 As shown, from bottom to top, it includes a transparent conductive substrate layer (ITO), a composite hole transport layer (SAM and Al2O3), a perovskite absorber layer (perovskite thin film, PVK), a passivation layer (PEAI), an electron transport layer (PCBM), a buffer layer, and a metal back electrode layer (Ag).

[0039] The above-mentioned method for fabricating inverted perovskite solar cells includes the following steps: (1) Clean the transparent conductive substrate layer Take ITO transparent conductive glass and clean it three times with detergent and deionized water, and then clean it twice with ethanol for 20 minutes each time. Before use, clean it in a UV ozone cleaner for 100 seconds.

[0040] (2) Preparation of composite hole transport layer Preparation of 20 mg / mL nano nickel oxide (NiO) x , containing Ni 2+ and Ni 3+ The aqueous solution was spin-coated onto a transparent conductive substrate at 3000 rpm for 30 s, and then annealed at 150°C for 30 min.

[0041] Prepare a 0.5 mg / mL MEO-2PACz ethanol solution and spray it onto the above-mentioned NiO-coated substrate at a speed of 3000 rpm. x Spin-coating was performed on a transparent conductive substrate for 30 seconds, followed by annealing at 100°C for 10 minutes to form an interface modification layer.

[0042] Prepare an Al2O3 dispersion (volume ratio 1:40, solvent isopropanol), spin-coat it onto the transparent conductive substrate coated with MEO-2PACz at a speed of 4000 rpm for 30 s, and anneal it at 100 °C for 15 min.

[0043] (3) Preparation of perovskite absorber layer (perovskite thin film) 1.6 mol of lead iodide, 1.6 mol of formamidinium hydroiodate (FAI), 0.075 mol of cesium iodide, 0.15 mol of methylamine iodide (MAI), and 0.1875 mol of methylamine hydrochloride (MACl) were dissolved in 1 mL of a mixture of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), wherein the volume ratio of DMF to DMSO was 4:1. The mixture was stirred at room temperature for about 20 h to prepare a perovskite precursor solution. 4 mg of (Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino)ethyl acetate (ATTBA) was dissolved in 1.0 mL of DMSO to obtain an additive solution with a concentration of 4 mg / mL. The additive solution is then dissolved in the perovskite precursor solution to obtain the perovskite precursor solution with additives. Take the above-mentioned perovskite precursor solution with additives, spin coat it on the interface modification layer at a speed of 4500 rpm for 45s, add 200 μL of chlorobenzene in the last 10s, and heat it at 150℃ for 30min to obtain the perovskite absorber layer.

[0044] The structural formula of the (Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino)ethyl acetate (ATTBA) is as follows: (4) Preparation of passivation layer Dissolve 1.5 mg of PEAI (phenylethyl ammonium iodide) in 1 mL of isopropanol, spin coat it onto the perovskite absorber layer at a rotation speed of 3000 rpm and an acceleration of 2000 rpm / s for 30 s, and then anneal it at 70℃ for 5 min to obtain a passivation layer.

[0045] (5) Fabrication of electron transport layer and buffer layer Dissolve 20 mg of PCBM in 1 mL of chlorobenzene, spin coat the passivation layer at 2000 rpm for 30 s, and then anneal at 90 °C for 30 min to obtain the electron transport layer.

[0046] Dissolve 0.5g of BCP in 1mL of ethanol and spin coat it onto the electron transport layer at 5000 rpm for 30 s without annealing to obtain a buffer layer.

[0047] (6) Preparation of metal electrodes A cathode silver film with a total thickness of 100 nm was deposited on the buffer layer to obtain an inverted perovskite solar cell.

[0048] The effective area of ​​the prepared inverted perovskite solar cell is 0.04 cm².

[0049] Comparative Example 1 This comparative example is basically the same as the example, except that in step (3), ethyl acetate (Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino)acetate (ATTBA) is not added.

[0050] Comparative Example 2 This comparative example is basically the same as the example, except that in step (3), "take another 100 μL of additive solution with a concentration of 4 mg / mL and dissolve it in 1.0 mL of perovskite precursor solution to obtain perovskite precursor solution with additive" is changed to "take another 100 μL of additive solution with a concentration of 2 mg / mL and dissolve it in 1.0 mL of perovskite precursor solution to obtain perovskite precursor solution with additive".

[0051] Comparative Example 3 This comparative example is basically the same as the example, except that in step (3), "take another 100 μL of additive solution with a concentration of 4 mg / mL and dissolve it in 1.0 mL of perovskite precursor solution to obtain perovskite precursor solution with additive" is changed to "take another 100 μL of additive solution with a concentration of 6 mg / mL and dissolve it in 1.0 mL of perovskite precursor solution to obtain perovskite precursor solution with additive".

[0052] Comparative Example 4 This comparative example is basically the same as the example, except that in step (3), “(Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino)ethyl acetate (ATTBA)” is replaced with “2-(2-amino-4-thiazolyl)-2-oxoethyl acetate (EAOA)”.

[0053] The structural formula of ethyl 2-(2-amino-4-thiazolyl)-2-oxoethyl acetate (EAOA) is as follows: Example 1: PCE Statistical Chart of Perovskite Solar Cells Modified with Different Additives Figure 2The graph shows the power conversion efficiency (PCE) of the inverted perovskite solar cells prepared in Comparative Example 1, Example 1, and Comparative Example 4. As can be seen from the graph, the average efficiency of the device with ATTBA additive reached 25.24%, significantly higher than the 24.41% of the control group without additive and the 24.43% of the EAOA-modified device. This indicates that, compared to EAOA, ATTBA molecules can more effectively synergize with the perovskite precursor: on the one hand, they significantly slow down the crystallization rate and increase the grain size; on the other hand, through multi-target coordination and hydrogen bonding of thiazole rings, amino groups, and ester groups, they more effectively passivate grain boundaries and surface defects, thereby reducing non-radiative recombination losses, improving the open-circuit voltage and fill factor of the device, and ultimately achieving higher power conversion efficiency.

[0054] Example 2: PCE statistics of perovskite solar cells with different concentrations of ATTBA modification Figure 3 The figure shows the PCE statistics of ATTBA-modified perovskite solar cells at different concentrations. The performance of Comparative Example 1 and devices with ATTBA concentrations of 2 mg / mL (Comparative Example 2), 4 mg / mL (Example 1), and 6 mg / mL (Comparative Example 3) are compared. The results show that the device with the highest PCE and best repeatability is at a concentration of 4 mg / mL. However, at too low a concentration (2 mg / mL), the additive's crystallization regulation and defect passivation are insufficient, resulting in more residual defects in the film and lower efficiency. At too high a concentration (6 mg / mL), additive aggregation or the formation of an insulating interface layer may hinder carrier transport, leading to performance degradation. Therefore, 4 mg / mL is the preferred ATTBA concentration in this invention, as this condition achieves the best balance between optimized crystallization kinetics and defect passivation, resulting in optimal photoelectric conversion efficiency.

[0055] Example 3: Interaction between additive ATTBA and perovskite precursor solution ATTBA was physically mixed with PbI2 and FAI in equal mass ratios, and then subjected to FTIR testing. Figures 4-5 As shown in the figure. The results show that the NH stretching vibration peak of the ester group in the ATTBA molecule changes by about 3–10 cm⁻¹ after mixing with PbI₂ and FAI. -1 The red shift of the peaks and the shift of the characteristic peaks of C=N and CS in the thiazole ring to varying degrees indicate that the amino group, nitrogen atom, and sulfur atom in the thiazole ring of the ATTBA molecule all participate in the interaction with Pb. 2+ It coordinates with FAI and also interacts with it through hydrogen bonds and other mechanisms. These intermolecular interactions are the basis for ATTBA's ability to regulate crystallization and passivate defects.

[0056] Example 4: Characterization of the surface morphology of perovskite thin films Figure 6 The image shows a SEM image of the perovskite absorber layer prepared in Comparative Example 1 (without any additives). It can be seen that the control film has smaller grain size, denser and unevenly distributed grain boundaries, and more pinholes and defects. This is due to the excessively fast crystallization rate and insufficient nucleus growth when no additives are added to regulate the crystallization. Figure 7 The image shows a SEM image of the perovskite absorber layer prepared in Example 1 (with the addition of the ATTBA additive of this invention). It can be clearly seen that the film grain size is significantly increased, grain boundaries are significantly reduced, and the film surface is dense, smooth, and free of pinholes, exhibiting excellent quality. This is attributed to the synergistic effect of the thiazole ring (sulfur and nitrogen atoms) and amino polyfunctional groups contained in the ATTBA molecule.

[0057] Example 5: Defect passivation effect of perovskite thin films like Figure 8 The steady-state photoluminescence (PL) spectra of the perovskite absorber layers prepared in Example 1 and Comparative Example 1 are shown. The results indicate that the PL intensity of the film in Example 1 is significantly increased compared to Comparative Example 1, indicating that nonradiative recombination is significantly suppressed. This demonstrates that the ATTBA additive effectively passivates defects in the film through the synergistic effect of multiple functional groups, significantly reducing the probability of nonradiative recombination and thus improving the photovoltaic performance of the device.

[0058] Example 6: Photoelectric Performance Testing The photovoltaic performance of the inverted perovskite solar cells prepared in Example 1 and Comparative Example 1 was tested. Test conditions: simulated AM1.5G illumination (1000 W / m²), NREL-calibrated standard silicon cells were used to calibrate the light source intensity, the test temperature was 25±2℃, the voltage scan range was -0.2~1.3 V, and the step size was 10 mV. The test results are as follows: Figure 9 As shown in the figure. The results show that the photoelectric performance of the device in Example 1 is significantly better than that of the device in Comparative Example 1. This indicates that due to the combined effect of the ATTBA additive on optimizing the crystallization process and passivating defects, all photovoltaic parameters of the device are significantly improved.

[0059] Example 7: Stability Test The packaged devices of Example 1 and Comparative Example 1 were subjected to stability testing (aging in a nitrogen atmosphere at 85°C). Figure 9 As shown in the results, Comparative Example 1 exhibits a faster degradation trend after 1200 hours, while Example 1 demonstrates excellent stability. These results validate the significant effect of the ATTBA additive in improving the long-term stability of perovskite solar cells.

[0060] In summary, the thiazole passivator provided by this invention achieves preferred orientation of the (100) / (200) crystal plane through a unique molecular structure design, while delaying the crystallization process, improving crystal quality, significantly reducing non-radiative recombination loss, and enhancing device efficiency and long-term stability. This endows perovskite solar cells with higher photoelectric conversion efficiency and excellent environmental / operational stability. It has the advantages of simple structure, feasible synthesis, and good process compatibility, and is suitable for the preparation of high-efficiency, long-life perovskite photovoltaic devices.

[0061] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. The application of a thiazole derivative additive in the preparation of perovskite thin films, characterized in that, The thiazole derivative additive is (Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino)ethyl acetate.

2. The application according to claim 1, characterized in that, The method of application includes: adding the thiazole derivative additive to a perovskite precursor solution to prepare a perovskite thin film; In the perovskite precursor solution, the concentration of the thiazole derivative additive is 3.0–5.0 mg / mL.

3. A perovskite thin film containing a thiazole derivative additive, characterized in that, The thiazole derivative additive is (Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino)ethyl acetate; The perovskite thin film has the structural formula ABX3, where A is an organic cation or metal ion selected from CH(NH2)2. + CH(NH2)2 + and Cs + One or more of them, B is selected from Pb 2+ Sn 2+ One or more of them, where X is I - ,Br - and Cl - One or more of them.

4. The method for preparing the perovskite thin film according to claim 3, characterized in that, The preparation method includes the following steps: Preparation of perovskite precursor solution; The thiazole derivative additive was added to the perovskite precursor solution to obtain a mixture; The mixture is coated onto a substrate, an antisolvent is added dropwise, and the mixture is annealed to obtain the perovskite film.

5. The preparation method according to claim 4, characterized in that, The preparation method includes the following specific steps: Formamidin hydroiodide, lead iodide, methylamine hydrochloride, cesium iodide, and methylamine iodide were dissolved in DMF / DMSO solvent to obtain a perovskite precursor solution. The thiazole derivative additive was dissolved in DMSO to obtain an additive solution; The additive solution is dissolved in the perovskite precursor solution to obtain a mixture; The mixture is coated onto a substrate with an interface modification layer. The mixture is then spin-coated at 4000-5000 rpm for 40-50 seconds. An antisolvent is added dropwise in the last 10-15 seconds, followed by annealing to obtain the perovskite film. The antisolvent includes at least one of anisole, chlorobenzene, and diethyl ether.

6. The preparation method according to claim 5, characterized in that, The annealing method includes heating at 100℃~150℃ for 30min~60min.

7. A reverse perovskite solar cell, characterized in that, Includes the perovskite thin film as described in claim 3.

8. The inverted perovskite solar cell according to claim 7, characterized in that, The inverted perovskite solar cell further includes a transparent conductive substrate layer, a composite hole transport layer, a passivation layer, an electron transport layer, and a metal back electrode layer. The material of the transparent conductive substrate layer is selected from any one or more of indium tin oxide, fluorine-doped tin oxide, and aluminum-doped zinc oxide. The composite hole transport layer comprises a hole transport layer, an interface modification layer, and an insulating modification layer arranged sequentially. The material of the hole transport layer is selected from nano-nickel oxide, the material of the interface modification layer is selected from one or more of MEO-4PACz, MEO-2PACz, and 4PADCB, and the material of the insulating modification layer is selected from Al2O3. The material of the passivation layer is selected from any one or more of phenethyl ammonium iodide, 1,3-diaminopropane dihydroiodate, piperazine dihydroiodate, and piperazine hydroiodate. The material of the electron transport layer is selected from any one or more of PCBM, C60, BCP, and SnO2; The material of the metal back electrode layer is selected from one or more of Ag, Au, and Cu.

9. The inverted perovskite solar cell according to claim 7, characterized in that, The band gap of the inverted perovskite solar cell is 1.56 eV.

10. The method for preparing an inverted perovskite solar cell according to any one of claims 7 to 9, characterized in that, The preparation method includes: S1. Clean the transparent conductive substrate layer; S2. Preparation of the composite hole transport layer: Prepare an aqueous solution of 18-22 mg / mL nickel nanoparticles, spin-coat it onto a transparent conductive substrate at 2500-3500 rpm for 25-35 s, and then anneal it at 145-155℃ for 25-35 min; Prepare an ethanol solution of 0.4-0.6 mg / mL MEO-2PACz, spin-coat it onto a transparent conductive substrate coated with nickel nanoparticles at 2500-3500 rpm for 25-35 s, and anneal it at 95-105℃ for 5-15 min to form an interface modification layer; Prepare an Al2O3 dispersion, spin-coat it onto a transparent conductive substrate coated with MEO-2PACz at 3500-4500 rpm for 25-35 s, and anneal it at 95-105℃ for 10-20 min; S3. Preparation of perovskite thin films: 1.6 mol of lead iodide, 1.6 mol of formamidinium hydroiodate, 0.075 mol of cesium iodide, 0.15 mol of methylamine iodide, and 0.1875 mol of methylamine hydrochloride were dissolved in 1 mL of a mixture of N,N-dimethylformamide and dimethyl sulfoxide, wherein the volume ratio of DMF to DMSO was 4:

1. The mixture was stirred at room temperature for about 20 h to obtain a perovskite precursor solution. The thiazole derivative additive was dissolved in DMSO to obtain an additive solution. The additive solution was then dissolved in the perovskite precursor solution to obtain a mixture. The mixture was coated onto a substrate with an interface modification layer. The interface modification layer was first spin-coated at 4000-5000 rpm for 40-50 s, and an antisolvent was added dropwise in the last 10-15 s. After spin-coating, the conductive substrate was placed on a hot plate at 100°C. Heating at 150℃ for 30 to 60 minutes and then cooling to form a perovskite film, thus obtaining the perovskite film; S4. Preparation of passivation layer: Dissolve phenylethyl ammonium iodide in isopropanol, spin coat it on the perovskite film at a speed of 2500~3500 rpm for 25~35 s, and then anneal it at 65~75℃ for 4~6 min to obtain the passivation layer. S5. Preparation of electron transport layer and buffer layer: Dissolve PCBM in chlorobenzene, spin coat it on the passivation layer at a speed of 1500~2500 rpm for 25~35 s, and then anneal it at 85~95℃ for 25~35 min to obtain electron transport layer. Dissolve BCP in ethanol and spin coat it onto the electron transport layer at a speed of 4500~5500 rpm for 25~35 s to obtain a buffer layer; S6. Preparation of metal electrodes: Cathode silver is deposited on the buffer layer, with a total silver film thickness of 80~120 nm, to obtain an inverted perovskite solar cell.